(untitled) (The Review of Diabetic Studies, 2025)
Rapid identification, effective medications, and controlling infection spread makes emergency medicine and respiratory disease out of sync with conventional medical practice flow. The current study builds on the experience of emergency service collaboration with radiology, pharmacy, and health security focusing on the management of emergency cases involving pneumonia, COPD, asthma, pulmonary embolism, and COVID-19, among other conditions. The coordinated partnership of the clinics with pharmacy and infection control concluded the reviewers of literature, clinical protocols, and other health measures taken during the pandemic that systematic collaboration saves more lives by eliminating clinical lag time, overriding rational drug use, and preventing the transmission of infection within the healthcare system. The studies showed that the implementation of rapid imaging studies in the emergency department resulted in the diagnosis of life-threatening conditions in 90% of patients, a 40% reduction in adverse drug events (ADEs), 35% of patients were treated and returned home safely 35% more frequently, and their respiratory infections were non-hospital acquired. The case studies predict the impact of pathway integration on clinical and other outcomes, including the use of emergency CT pulmonary embolism profiles, the pharmacist’s role in antibiotic guidance, prescribed drugs on safe isolation, and other respiratory infections. The study cannot demonstrate the benefits of system integration due to integration deficiencies and system disruptions in communication, professional training, and resource apportioning. The study surveys system integration and inter-professional system improvements on emergency medicine. Integrated emergency care plays a vital role in emergency care management for sustaining safety and efficacy in the management of critical care of reactive respiratory ailments.